Magi. 18 : the labyrinth of magic - Otaka, Shinobu (VIZ Media, 2016)
"The army of Leam reaches the gates of Magnoshutatt, and the magicians of the city join the battle. Aladdin is among them, fighting to protect his friend Titus, and his skills are crucial to the defense. But what will happen when Aladdin must face the full might of Leam's team of Fanaris warriors?" -- page 4 of cover.